(untitled) (Proceedings of the International Conference on Food, Nutrition, Health and Lifestyle, 2025)
Alpha-lipoic acid (ALA) has various effects on health, one of which is its impact on lipid levels in the blood. Preclinical studies have demonstrated this effect. Nonetheless, the outcomes of clinical evaluations have been contradictory. Systematic reviews on this subject have also yielded conflicting findings. This study conducted a systematic review and meta-analysis of randomized controlled trials to evaluate the effects of ALA on changes in various blood lipid levels. We discovered that ALA significantly reduced triglyceride (TG) levels (-6.299 mgdL-1 95% CI -10.104 to -2.494); however, the studies contributing to this significant finding were found to confer a high risk of bias. In contrast, no significant effects were observed on the levels of total cholesterol (TC; 0.304 mgdL-1 95% CI -3.436 to 4.044), High-density Lipoprotein (HDL; -1.460 mgdL-1 95% CI -5.445 to 2.525), or Low-density Lipoprotein (LDL; 0.226 mgdL-1 95% CI -0.711 to 1.163). Although the dose of ALA and the duration of administration did not show statistically significant effects, it was observed that ALA doses not exceeding 1,200 mg per day and administration for approximately 16 weeks were more effective in reducing TG levels. We discovered that our study also contained research with small sample sizes and high degree of heterogeneity between studies. These findings highlight the potential lipid-modifying consequence of ALA, especially triglyceride-lowering effect, emphasizing the prominence of appropriate dosing along with duration of treatment.